Excitons in Quantum Systems 0-2D - Claudio Lucas Nunes de Oliveira (2005)
In the last few decades the physics of low dimensional semiconductor systems have attracted much attention due to the potential applications that arise from their due to electronic and optical properties. For example, InGaAs and InGaAsP heterostructures are currently used in optoelectronic applications that operate in the infrared spectrum. In such systems, the con_nement of charges can be realized in one, two or in three dimensions. The optical properties of quantum con_nement systems are basically determined by electronic transitions. Excitons, formed by an electron-hole pair bounded by coulombic interaction, are the responsible for the emission wavelenght. The aim of this work is to computer the ground state exciton energies in quantum wells, cylindrical quantum wires and pyramidal quantum dots as a function of the their size and shape. The results show that the exciton energies of In0:4Ga0:6As/GaAs quantum wells and wires are in the range from 0.9 to 1.3 eV. The results of In0:4Ga0:6As/GaAs pyramidal quantum dots show that the e-lh (e-hh) recombination energies are approximately 1.3-1.4 (1.18-1.28) eV